The Jim Crow Routine : Everyday Performances of Race, Civil Rights, and Segregation in Mississippi - Berrey, Stephen A. (Book collections on Project MUSE., 2015)
The South's system of Jim Crow racial oppression is usually understood in terms of legal segregation that mandated the separation of white and black Americans. Yet, as this work shows, it was also a high-stakes drama that played out in the routines of everyday life, where blacks and whites regularly interacted on sidewalks and buses and in businesses and homes. Every day, individuals made, unmade, and remade Jim Crow in how they played their racial roles-how they moved, talked, even gestured. The highly visible but often subtle nature of these interactions constituted the Jim Crow routine.